Systemic oxidative stress and circulating long non-coding RNAs as potential novel cardiovascular risk factors in the general population - Rodríguez Sánchez, E.; Mohammed, S.; Navarro-García, J.; Mercado-García, E.; Calvo, E.; González-Quintela, A.; Ruilope, L.; Paneni, F.; Ruiz-Hurtado, G. (Atherosclerosis, 2024)
Background and Aims: A significant proportion of the general population escape CVR lowering approaches basing on the currently used CVR estimators, which mostly rely on traditional CVR factors. We studied systemic oxidative stress and circulating long non-coding RNAs (lncRNAs) as potential novel CVR factors. Methods: Systemic oxidative stress was assessed by OxyScore and AntioxyScore in 896 adults (17-65 years old) considering <30 years old as controls. Standardized values of carbonyl groups, 8-hydroxy-2'-deoxyguanosine, and oxidized LDL were included in OxyScore, and total antioxidant capacity, catalase activity, and superoxide dismutase activity in AntioxyScore. lncRNAs CoroMarker, KCNQOT1, UCA1, LeXis, MALAT-1, MIAT and Wisper were measured in plasma of a subset of 142 patients. CVR was determined by QRisk-lifetime. Results: OxyScore and AntioxyScore were associated with CVR independently of sex and age (p<0.05), traditional CVR factors (smoking, SBP, cholesterol, LDL, blood glucose, BMI, eGFR, family history; p<0.01), and antihypertensive (p<0.001) and statin (p<0.01) treatments. Circulating KCNQ1OT1 correlated with age and blood glucose (p<0.05 and p<0.01), UCA1 with LDL (p<0.05), and CoroMarker, UCA1, and LeXis with cholesterol (p<0.05). Interestingly, Wisper was associated with OxyScore (p<0.01) independently of traditional CVR factors. Conclusions: The association between systemic oxidative stress and CVR suggests that integrating multimarker scores such as OxyScore and AntioxyScore into CVR estimators might improve CVR assessment. Moreover, we show for the first time the associations between a panel of lncRNAs and traditional CVR factors, pointing to their potential as clinical biomarkers. Finally, we describe Wisper as a novel lncRNA associated with oxidative stress, and which specific role deserves further investigation.
Keywords: oxidative stress; cardiovascular risk factors; long non-coding RNAs; JCR; WOS(2)